Earnings Management in Domestic and Foreign IPOs in the United States: Do Home Country Institutions Matter?. Issue 2 (14th March 2020) - Filatotchev, Igor; Jona, Jonathan; Livne, Gilad
Abstract : Using a large sample of domestic and foreign IPOs in the US, we investigate how threats of enforcement by the Securities and Exchange Commission (SEC) and private litigation influence earnings management in IPO prospectuses. We propose that perceptions of foreign institutions may influence SEC enforcement action and private litigation. We provide evidence that enforcement and litigation threats are negatively related to the strength of legal institutions in the foreign IPO's country of origin. We find earnings management is more pronounced in foreign IPOs from countries with strong legal institutions. We further explore whether earnings management is priced in the IPO market and find no relation between IPO proceeds and earnings management. Our results are consistent with upward earnings management as in Stein (1989), the magnitude of which is reduced when the anticipated cost of enforcement and litigation is higher. Collectively, our results cast doubt on the validity of the bonding hypothesis.